A thereto-economical optimization of a domestic solar heating plant with seasonal storage - Ucar, A.; Inalli, M. (Pergamon-Elsevier Science Ltd, 2007)
In this study, the thereto-economic optimization analysis to determinate economically optimal dimensions of collector area and age volume in domestic solar heating systems with seasonal storage is presented. For this purpose, a formulation based on the P-1 and P-2 method is developed and solved by using MATLAB optimization Toolbox for five climatically different locations of The results showed that the required optimum collector area in Adana (37 degrees N) for reaching maximum savings is 36 m(2)/house 65 m(2)/house in Erzurum (39 degrees N) for same storage volume (1000 m(3)). The effects of collector efficiency on solar fraction and are investigated. The simulation results showed that the solar fraction and savings of the selective flat plate collector systems are than the other black paint flat plate collector systems. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: solar heating; thereto-economic; optimization